2015
DOI: 10.1161/circoutcomes.114.001335
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Quality of Life Outcomes After Transapical Transcatheter Aortic Valve Replacement

Abstract: Background In the PARTNER randomized controlled trial (RCT), which represented the first exposure to transapical transcatheter aortic valve replacement (TA-TAVR) for many clinical sites, high risk patients undergoing TA-TAVR derived similar health-related quality-of-life (HRQoL) outcomes when compared with surgical AVR (SAVR). With increasing experience, it is possible that HRQoL outcomes of TA-TAVR may have improved. Methods and Results We evaluated HRQoL outcomes at 1-, 6-, and 12-month follow-up among 875… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…However, TA-TAVR is associated with higher mortality and prolonged recovery when compared with TF-TAVR, and unlike TF-TAVR, health-related quality of life after TA-TAVR is no better than SAVR. 19,20 Our study showed that TA-TAVR is also associated with an increased risk of 30-day readmission. This association may be influenced by residual confounding as patients undergoing TA-TAVR are typically sicker with more complex PVD that cannot be captured completely in an administrative database such as the NRD.…”
Section: Discussionmentioning
confidence: 68%
“…However, TA-TAVR is associated with higher mortality and prolonged recovery when compared with TF-TAVR, and unlike TF-TAVR, health-related quality of life after TA-TAVR is no better than SAVR. 19,20 Our study showed that TA-TAVR is also associated with an increased risk of 30-day readmission. This association may be influenced by residual confounding as patients undergoing TA-TAVR are typically sicker with more complex PVD that cannot be captured completely in an administrative database such as the NRD.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, both changes were higher relative to SAVR. Moreover, a few studies assessed other validated measures of functional status such as the Kansas City Cardiomyopathy Questionnaire (KCCQ), and similar clinically important and favorable changes were observed in high-risk and in-operable patients aged 80 years and over (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Transapical access for TAVR is an accepted approach for patients in whom vascular anatomy do not permit a transfemoral approach and if on one hand it avoids potential site complications of iliac and femoral vessels, on the other hand has some limitations including an increase in respiratory complications[11]. …”
Section: Clinical Evaluationmentioning
confidence: 99%